Neonatal tetanus in Libreville, Gabón. Two Case Reports - Rafael Ferrer Montoya; Alfredo Jiménez Nogueras; Odalis Lourdes Guerra Pompa; Alexei Capote Vázquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Neonatal tetanus is an infection caused by Clostridium tetani bacterium, which usually enters the body through a skin wound. It is more common in developing countries. The infection generally starts in the umbilical cord (septic cutting of the cord). Diagnosis is primarily based on the clinical examination of the newborn. Not receiving the tetanus vaccine and its reactivation during pregnancy are important aspects to consider. Two similar clinical cases are presented, one of them was discharged and the other died, after a short hospital stay. These reports are aimed at emphasizing the current status of a health problem persisting in many countries. In relation to Gabon, the disease has not been eradicated despite the free vaccination system available in the country.